Planar 99mTc-PSMA Imaging of Prostate Cancer in a Low-Resource Setting: A Series Report - Orunmuyi, A.T.; Oladeji, A.A.; Azodoh, E.U.; Omisanjo, O.A.; Olapade-Olaopa, E.O. (World Journal of Nuclear Medicine, 2022)
Objective Technetium-99m labeled prostate-specific membrane antigen (PSMA) single-photon emission computed tomography/computed tomography (SPECT/CT) is a suitable alternative to prostate-specific membrane antigen-positron emission tomography (PSMA-PET) imaging. However, the availability of SPECT/CT in many developing countries is limited.Materials and Methods To evaluate the utility of planar 99mTc-PSMA in the absence of SPECT/CT, we compared planar 99mTc-PSMA and routine bone scan imaging in low-, intermediate-, and high-risk prostate cancer in five patients with histologically confirmed prostate cancer who had both scans within a period of less than 4 days. The mean age of patients was 66.8 ± 5.24, and the median prostate-specific antigen level was 175 ng/mL (range: 0–778 ng/mL).Results Planar 99mTc-PSMA scan provided no additional benefit over bone scans in the low-risk prostate cancer cases. In the cases with intermediate-risk prostate cancers, planar 99mTc-PSMA indicated complete and partial response to treatment in oligometastatic and widespread metastatic disease, respectively. In one patient with high-risk prostate cancer, planar 99mTc-PSMA detected additional skeletal lesions that were not seen on bone scan.Conclusion In the absence of SPECT/CT, planar 99mTc-PSMA was useful for confirming extent of disease in treated intermediate- and high-risk prostate cancer. It showed little value in low-risk prostate cancer, especially when bone scan is normal. It was particularly useful for treatment response assessment in oligometastatic disease, and its utility should be further explored.
Keywords: planar 99mTc HYNIC PSMA; bone scan; equivocal scans; SPECT